PERANCANGAN DAN SIMULASI SISTEM OFFGRID PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) UNTUK TOWER BTS 1500WATT: Kukuh Aris Santoso - Jurnal, Redaksi Tim (ENERGI & KELISTRIKAN, 2019)
In this paper discusses the design of solar power plants (SPP) is used for BTS tower1500 watt with a off grid systems. Design is calculated technically and simulated with computer software to determine an estimate of the electrical energy produced by the solar module. And also, count the use of the battery if there is no sun or autonomy days.